Mythical representation of the world and male domination among Greek Pomacs - Vernier, Bernard (The Greek Review of Social Research, 1981)
This survey, which is part of a research program into domination and/or exploitation relationshpis within the Greek family tries to avoid falling into the double trap of theoretical formality on the one hand and monography with no problematical dimension on the other. Using the case study method, the analysis of relationships between the sexes in a Pomac village enables us to analyse a particular type of domination through which the exploitation of women becomes a reality in some rural societies. The sexual divisions of labour amongst the Pomacs cannot be understood without reference to the system of mythical oppositions which shapes all practices and divides them into male or female categories. The apparent contradictions can be explained by the technaeconomical as well as logical problems mythical thought is faced with when materializing in the division of labour. However, if mythical thinking can escape contradictions, it is because it classifies activities according to different categories of classification by perceiv ing every activity in multiple dimensions: the location, the required posture, the relatively dirty nature of the work, etc. In their dominant position in the production relations, the men find ideological conditions within the mythical oppositions to. main tain their domination. The mythical «rationale» screens domination and exploitation relationships since it grounds each sex’s position on the nature of things, since it tends to continuously provide proof ofits genuinity and because it is relatively autonomous as regards the domination and exploitation relationships it implies. Moreover, by relegating women to a closed environment, by excluding them from schools and cinemas, by separating them from money, the mythical «rationale» becomes the basis of their total dependence and deprives them of the intellectual tools and material means necessary for their liberation. Due to theirdominant position, the men have had the opportunity of reinforcing their position through the changes caused by the opening-up of Pomac society towards the outside world. These changes have meant more work for and, above all, greater devalua tion of women. In the future however, those changes will be agents responsible for women’s liberation, as already shown in the ap pearance of an acute awareness of their exploitation among young girls.